2014
DOI: 10.4236/aasoci.2014.410027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Catha edulis</i> (Khat) Chewing and Its Associated Factors among Ataye Secondary School Students in Northern Shoa, Ethiopia

Abstract: The life time and current prevalence of khat chewing are 15.36% (95% CI; 11.7, 19.8) and 13.25% (95% CI; 11.0, 18.1) respectively. Multivariable logistic regression model revealed that male students [Adjusted OR = 2.15 (95% CI; 1.02, 4.56)], presence of chewer friends [Adjusted OR = 3.14 (95% CI; 1.53, 6.41)], having chewer family [Adjusted OR = 2.68 (95% CI; 1.13, 6.37)] and place of residency [Adjusted OR = 1.89 (95% CI; 1.0, 3.79)] were associated risk factors for khat chewing. Khat chewing is prevalent amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 15 publications
9
40
0
1
Order By: Relevance
“…However, our study findings were nearly similar with findings from ahospital based study carried out in Dessie, northeast Ethiopia (66.94%) [35]. Khat use was more prevalent among male patients than female patients (75.3% vs.34.7%), which is in line with the previous Ethiopian studies from Gondar, Jimma, Ataye and Dilla [30,31,36,37].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our study findings were nearly similar with findings from ahospital based study carried out in Dessie, northeast Ethiopia (66.94%) [35]. Khat use was more prevalent among male patients than female patients (75.3% vs.34.7%), which is in line with the previous Ethiopian studies from Gondar, Jimma, Ataye and Dilla [30,31,36,37].…”
Section: Discussionsupporting
confidence: 92%
“…The odds of using khat in males were 5.8 times higher as compared with females. The findings in our study were comparable with a school and college based study conducted in Ataye and Bahirdar, Ethiopia [37,38].…”
Section: Khat Use Cor(95% Ci) Aor(95% Ci) P-valuesupporting
confidence: 90%
“…Being male sex had a significant role to be user as compared to females. This finding is line with studies conducted in Ethiopia [2,36,[47][48][49][50][51]. This significant difference between male and female may be justified as; females are less exposed to chewing practice than males.…”
Section: Discussionsupporting
confidence: 91%
“…After calculating for all possible sample sizes, we selected the bigger sample size sufficient enough to address all research objectives. The bigger sample size obtained in this study was calculated using the reported proportions of khat chewing for urban(8.73%) and rural (4.52%) at 95% confidence level and power of 90% 37 . The study from which we took the proportion showed that, living in an urban area was an exposure variable than living in rural.…”
Section: Methodsmentioning
confidence: 99%